Pengembagan Pariwisata Oleh Dinas Pariwisata Dan Kebudayaan Kabupaten Bangli - Satria Dalem, I Gusti Agung Bagus; Sastra Wijaya, Komang Adi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2021)
The Tourism and Culture Office Bangli Regency to develop the tourism sector is guided by RIPPDA (Regional Tourism Development Master Plan). However, in the development of tourism in Bangli Regency is relatively slow caused the competence of human resources of tourism; decrease in tourist visits due to the Covid-19 Pandemic; budget; accessibility ; and the lack of new DTW tourism promotions The purpose of the research is to find out the extent of the implementation strategy by the Tourism and Culture Office Bangli Regency to efforts development of regional tourism . The strategy analysis using strategic planning by John M. Bryson and SWOT analysis ( Strength, Weakness, Opportunities, Threat ) . The type of research is descriptive-qualitative. The technique of determining the information is purposive sampling. This research resulted in an alternative strategy WO (Weaknesses-Opportunitie alternative strategies. The improvement of the alternative strategy is to strengthen internal weaknesses and maximize opportunities in Bangli district. Keyword : Tourism Sector, Strategic Planning, SWOT Analysis